Alzheimer-Compound Identification Based on Data Fusion and forgeNet_SVM - Yang, Bin; Bao, Wenzheng; Hong, Shichai (Frontiers in Aging Neuroscience, 2022)
Rapid screening and identification of potential candidate compounds are very important to understand the mechanism of drug for treatment of Alzheimer’s disease (AD) and greatly promote the development of new drugs. In order to greatly improve the success rate of screening and reduce the cost and workload of research and development, this paper proposes a novel Alzheimer-related compound identification algorithm namely forgeNet_SVM. Firstly Alzheimer related and unrelated compounds are collected by data mining method from the literature databases. Three feature description methods (ECFP6, MACCS and RDKit) are utilized to obtain the feature sets of compounds respectively, which are fused into the all_feature set. All_feature set is input to forgeNet_SVM, in which forgeNet is utilized to give the importance of each feature and select the important features for feature extraction. The selected features are input to support vector machines (SVM) algorithm to identify the new compounds in Traditional Chinese Medicine (TCM) prescription. The experiment results show that the selected feature set performs better than all_feature set and three single feature sets (ECFP6, MACCS and RDKit). The performances of TPR, FPR, Precision, Specificity, F1 and AUC reveal that forgeNet_SVM could identify more accurately Alzheimer-related compounds than other classical classifiers.